2018
DOI: 10.1016/j.jpedsurg.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for postoperative recurrent Hirschsprung associated enterocolitis

Abstract: This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Finally, our study provides additional evidence concerning moderate to severe undernutrition, as it is significantly associated with poor postoperative outcomes, which is consistent with the results of previous studies identifying risk factors for recurrent HAEC and quality of life in patients with HSCR 11,26 . Ding et al reported the impact of preoperative nutrition support in patients with HSCR and refractory constipation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Finally, our study provides additional evidence concerning moderate to severe undernutrition, as it is significantly associated with poor postoperative outcomes, which is consistent with the results of previous studies identifying risk factors for recurrent HAEC and quality of life in patients with HSCR 11,26 . Ding et al reported the impact of preoperative nutrition support in patients with HSCR and refractory constipation.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, our study provides additional evidence concerning moderate to severe undernutrition, as it is significantly associated with poor postoperative outcomes, which is consistent with the results of previous studies identifying risk factors for recurrent HAEC and quality of life in patients with HSCR. 11 , 26 Ding et al reported the impact of preoperative nutrition support in patients with HSCR and refractory constipation. They demonstrated that at the 1‐month follow‐up, the incidence of postoperative complications was lower and nutrition status was significantly improved in the group of patients who received enteral nutrition (EN) for 2 weeks prior to surgery compared with those without EN support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations